COMPARATIVE ANALYSIS OF ACTIVITY RATIO BEFORE AND DURING PANDEMIC (2019-2020) ON THE FOOD & BEVERAGE SECTOR LISTED ON IDX - Limbong, Gwyneth; Malau, Harman (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2022)
The COVID-19 pandemic in Indonesia has shaken the country, from public health to economic conditions. This has led to the issuance of new policies from the government, one of which has an impact on the sales of companies. This study aims to examine whether there are differences in the company's activities using the activity ratio as a benchmark. The sample of this research is food and beverage companies listed on the IDX with purposive sampling method. The data analysis method used is descriptive statistics and normality test, while the average difference test uses the paired sample t-test and the wilcoxon signed-rank test. Paired sample t-test on current asset turnover shows that there is a difference between before and during the pandemic. Meanwhile, the results of inventory turnover show no difference before and during the pandemic. The wilcoxon signed-rank test for total asset turnover showed that there was a difference between before and during the pandemic. Meanwhile, accounts receivable turnover and account payable turnover showed no difference before and during the pandemic.